Social, Cultural, and Local Contexts in PAI - Ghina, Ghina Sofia Mahfuzah; Ani Cahyadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the integration of local wisdom into Islamic Religious Education (PAI) to enhance its relevance in addressing the challenges posed by Indonesia's diverse socio-cultural context. The primary aim of this research is to analyze the importance of incorporating local values into the PAI curriculum design to strengthen character development, promote cultural identity, and ensure that Islamic teachings are understood in a way that resonates with students' lived experiences. This research uses a qualitative approach, including literature reviews and case studies, to explore the application of local wisdom such as the phrase